Marketing health services - Thomas, Richard K., 1944- (Health Administration Press ; Association of University Programs in Health Administration, 2020)
"This book explains the traditional and contemporary approaches that healthcare marketers rely on and that enable healthcare organizations to rise above current trends and turmoil to position themselves for the future healthcare environment"--